Fascism and history : chapters in concept formation - Gregor, A. James 1929-2019 (Cambridge Scholars Publishing, 2019)
The term "fascism" or "fascist" appears with regularity in academic and lay accounts of past and contemporary politics. This volume deals with the term as a concept, and traces its evolution over almost a century, as it has been employed virtually every place on the globe. It has been applied to Xi Jinping's China, Vladimir Putin's Russia, and to Donald Trump's presidency in the United States. Written in a clear style--free of unnecessary jargon--the account is fully accessible to both professionals and lay persons. An Addendum to the text provides social science professionals with a bibli